Usability evaluation of ToAksara as Balinese script learning mobile application - Indrawan, Gede; Sariyasa, Sariyasa; Dewi, Luh Joni Erawati; Gitakarma, Made Santo; Gunawan, I Made Agus Oka; Pranata, Putu Ade (International Journal of Advances in Applied Sciences, 2025)
ToAksara application transliterates Latin text into Balinese script and has been used in high school teaching and learning activities in Buleleng Regency, Bali, Indonesia. This application was expected to provide comfort and satisfaction for students while learning the Balinese language and script. To measure the comfort and satisfaction level, a usability evaluation was carried out that focused on the application's end user. This research used a combination of concurrent think-aloud (CTA) and user experience questionnaire (UEQ) to evaluate ToAksara. In CTA, data collection involved nine respondents given a task scenario and expressing their problems or input. In UEQ, data collection involved 385 respondents who chose the value closest to their impression of 26 statements. Based on the analysis results, CTA produced several recommendations for improving the application regarding navigation, functionality, and errors. Based on the analysis, the user satisfaction results showed that all aspects were included in the excellent category. The aspects of attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty each produced a value of 2.144, 2.220, 2.385, 2.345, 2.139, and 2.101. The excellent category shows that ToAksara was included in the range of the top 10% of products compared to the UEQ benchmark.